Societies in Transition in Early Greece An Archaeological History - Knodell, Alex R. (University of California Press, 2021)
Situated at the disciplinary boundary between prehistory and history, this book presents a new synthesis of Late Bronze Age and Early Iron Age Greece, from the rise and fall of Mycenaean civilization to the emergence of city-states in the Archaic period. These centuries saw the growth and decline of varied political systems and the development of networks across local, regional, and Mediterranean scales. As a groundbreaking study of landscape, interaction, and sociopolitical change, Societies in Transition in Early Greece systematically bridges the divide between the Mycenaean period and the Archaic Greek world to shed new light on an often-overlooked period of world history. "This book reconfigures our understanding of early Greece on a regional level, beyond Mycenaean 'palaces' and across temporal boundaries. Alex Knodell's sophisticated arguments enable a fresh reading of the emergence of early Greek polities, revealing the microregions that put to the test overarching 'Mediterranean' models. His detailed study makes a convincing return to a comparative framework, integrating a 'small world' network and its trajectory with the larger picture of ancient complex societies." SARAH MORRIS, Steinmetz Professor of Classical Archaeology and Material Culture, University of California, Los Angeles "A comprehensive, thoughtful treatment of the time period before the crystallization of the ancient Greek city states." WILLIAM A. PARKINSON, Curator and Professor, The Field Museum and University of Illinois at Chicago "An important and must-read account. The strength of this book lies in its close analysis of the important different regional characteristics and evolutionary trajectories of Greece as it transforms into the Archaic and, later, the Classical world." DAVID B. SMALL, author Ancient Greece: Social Structure and Evolution